Wave attenuation by Cystoseira sensu lato in two shallow Mediterranean coastal waters - PAPADIMITRIOU, EVANGELOS; HANNACHI , AMEL; PAPADIMITRIOU, APOSTOLOS; BEYREM , HAMMOUDA; KEFALAS, IOANNIS; MAHMOUDI , EZZEDDINE; SELLEMI, BADDREDDINE; SMITH, CHRIS; PAPATHANASIOU, VASILIS; FRASCHETTI, SIMONETTA; DANOVARO, ROBERTO; ORFANIDIS, SOTIRIS (Mediterranean Marine Science, 2024)
Coastal protection from erosion is an important ecosystem service provided by marine vegetation. Seaweeds and seagrasses can attenuate wave action in coastal areas and increase sediment retention. Here we investigated for the first time the effects of erect Cystoseira sensu lato forests in attenuating the wave energy in two Mediterranean shallow areas (Greece and Tunisia). The hydrodynamic effects were measured using the dissolution rate of gypsum cones (fd) r. Experiments were carried out in Greece, on the species Ericaria barbatula, and in Tunisia on the species E. brachycarpa and Cystoseira crinitophylla. Wave attenuation was directly related to percent cover of these macroalgal forests under different spatial and temporal conditions. On average, Cystoseira s.l. forests with 100 % cover reduced the wave action by 38 % more than the control (0 % cover). This study shows that Cystoseira s.l. forests under specific conditions play a key role for protecting the Mediterranean coasts from erosion, and can present a nature-based solution as an alternative to unsustainable and costly artificial constructions.